O estrangeirismo no texto joralístico : as colunas sociais e o high society - Siqueira Filho, Boris Dimitri de (2009)
This research describes the use of the foreign words in the journalistic text in the social section of Diário de Pernambuco (DP), in the month of August, between the years of 1930 and 1950, period which preceded and followed the II World War, precisely during the years of 1939 and 1945. The aim of the work was to identify the historical process of appearance of the foreign words and its implication on socio-political factors with their borrowing. A study on the historical process showed that their usage was present since the colonial period and that they were initially introduced to the Portuguese language by the White, the Black and the Indian cultures. A study of how some grammarians, linguists and writers see the problem was done to compare their points of view about it. The results showed that foreign words were used not only as a refinement pattern to introduce the news, but as a way to give name to things that did not exist in the Portuguese language in that time. The results of this research showed that the use of foreign words on a newspaper do not represent a risk to the Portuguese Language, but a way to modernize the language